Neonatal Brain MRI and Motor Outcome at School Age in Children with Neonatal Encephalopathy: A Review of Personal Experience - Eugenio Mercuri; Anna L. Barnett (Neural Plasticity)
The aim of this paper is to review (i) the spectrum of neuromotor function at school age in children who had been born full-term and presented with neonatal encephalopathy (NE) and low Apgar scores and (ii) the relation between the presence/absence of such difficulties and neonatal brain MRI. Motor outcome appears to be mainly related to the severity of basal ganglia and internal capsule involvement. Severe basal ganglia lesions were always associated with the most severe outcome, microcephaly, tetraplegia, and severe global delay, whereas more discrete basal ganglia lesions were associated with athetoid cerebral palsy, with normal cognitive development or minor neuro-motor abnormalities. White matter lesions were associated with abnormal motor outcome only if the internal capsule was involved. Children with moderate white matter changes but normal internal capsule, had normal motor outcome at school age.